A Bright Future Managing Pension Funds Based on Sharia Principles - Erica Siska Amalia; Awathifur Rochimah; Triana Dani Maulana; Rinda Asytuti (Cigarskruie: Journal of Educational and Islamic Research, 2025)
A pension is a crucial part of the whole concept of retirement that ensures the financial security of the old age people of the society. With the increasing awareness of Islamic law among the masses, the sharia pension fund comes as the solution that merges the financing needs with the religious values. This sharia pension fund is engineered to be a secure source of income in the old age while the whole process and instruments are not just permitted by the law but are in accordance with the principles of Sharia. Sharia-compliant contracts are being used such as mudharabah and ijarah, and the Sharia Supervisory Council has the responsibility to ensure the Sharia rules are respected in the finance world. This is one of the ethical and fair-sector approaches in the global economy. This article provides an in-depth analysis of the definition and classification of a sharia pension fund along with the fund management and its benefits for ensuring financial security according to Islamic principles. It is therefore hoped that this concept can be referred to by individuals and institutions that are dedicated to the application of Islamic economic system as a means of long-term financial planning.